Endocannabinoid receptor blockade increases vascular endothelial growth factor and inflammatory markers in obese women with polycystic ovary syndrome. (7th October 2016) - Sathyapalan, Thozhukat; Javed, Zeeshan; Kilpatrick, Eric S.; Coady, Anne‐Marie; Atkin, Stephen L.
Summary: Context: Animal studies suggest that cannabinoid receptor‐1 (CB‐1) blockade reduces inflammation and neovascularization by decreasing vascular endothelial growth factor (VEGF) levels associated with a reduction in inflammatory markers, thereby potentially reducing cardiovascular risk. Objective: To determine the impact of CB1 antagonism by rimonabant on VEGF and inflammatory markers in obese PCOS women. Design: Randomized, open‐labelled parallel study. Setting: Endocrinology outpatient clinic in a referral centre. Subjects: Twenty patients with PCOS (PCOS) and biochemical hyperandrogenaemia with a body mass index of ≥30 kg/m 2 were recruited. Patients were randomized to 1·5 g daily of metformin or 20 mg daily of rimonabant. Main outcome measures: Post hoc review to detect VEGF and pro‐inflammatory cytokines TNF‐α, IL‐1β, IL‐1ra, IL‐2, IL6, IL‐8, IL‐10 and MCP‐1 before and after 12 weeks of treatment. Results: After 12 weeks of rimonabant treatment, there was a significant increase in VEGF (99·2 ± 17·6 vs 116·2 ± 15·8 pg/ml, P < 0·01) and IL‐8 (7·4 ± 11·0 vs 18·1 ± 13·2 pg/ml, P < 0·05) but not after metformin (VEGF P = 0·7; IL‐8 P = 0·9). There was no significant difference in the pro‐inflammatory cytokines TNF‐α, IL‐1β, IL‐1ra, IL‐2, IL6, IL‐8, IL‐10 and MCP‐1 following either treatment. Conclusion: This study suggests that rimonabant CB‐I blockade paradoxically raised VEGF and the cytokine IL‐8 in obese women with PCOS that may have offset the potential benefit associated with weight loss.